Dropped Head Syndrome: A Systematic Review. Issue 10 (December 2019) - Drain, Joseph P.; Virk, Sohrab S.; Jain, Nikhil; Yu, Elizabeth
Abstract : Study design: This study was a systematic review. Objectives: To reveal demographic factors, etiologies, response to treatment, and to propose a novel treatment algorithm for dropped head syndrome (DHS). Summary of background data: DHS is a rare condition defined by weakness of the cervical paraspinal muscles resulting in passively correctable flexion of the cervical spine. Patients present with neck pain, difficulty eating, and impaired horizontal gaze. Because of the rarity of DHS, a paucity of information exists with regard to demographics, etiology, and relative superiority of medical and surgical treatment. Materials and Methods: We conducted a systematic literature review by searching PubMed for "dropped head syndrome, " "chin on chest, " "isolated neck extensor myopathy" (INEM), and "camptocephalia." Inclusion criteria were English-language articles that applied a specific treatment regimen with outcome data. A binomial logistic regression analysis was then performed to determine which covariates (age, sex, and treatments) were predictive of a positive response to treatment. Results: A total of 129 patients were described in 74 studies. Mean age was 63.6 and 63% were female. More than two-thirds of all patients fell into just 4 diagnostic categories (isolated neck extensor myopathy, 31.8%; Parkinson's, 20.2%; myasthenia gravis, 12.4%; amyotrophic lateral sclerosis, 7.0%). Overall positive response to treatment was 64.3%; primary medical treatment (73.5%), immune suppression (78.9%), and a combination of both (87.5%). Surgery was 93.8% successful. A treatment algorithm focused on appropriate diagnosis, initial medical management, with surgical evaluation only after failure of medical treatment was proposed. Conclusions: Treatment for DHS starts with accurate diagnosis of the underlying etiology and is often associated with neuromuscular disease. A treatment algorithm for appropriate management of these patients was proposed. A trial of medical management and/or immunomodulators is warranted. Failing nonoperative management, surgery is predictive of a positive outcome. Level of Evidence: Level V.